2016
DOI: 10.1097/sla.0000000000001874
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor is a Repressor of Inflammation-associated Colorectal Tumorigenesis in Mouse

Abstract: Objective To determine the role of the aryl hydrocarbon receptor (AHR) in colitis-associated colorectal tumorigenesis. Summary Background Data Colorectal cancer (CRC) is the third most commonly diagnosed cancer in both men and women in United States. Chronic intestinal inflammation increases the risk for the development of CRC. We questioned the involvement of AHR, a transcriptional regulator for intestinal innate immunity and inflammation, in the colitis-associated tumorigenesis. Methods We used a mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 32 publications
5
60
3
Order By: Relevance
“…Although dioxin is classified as a human carcinogen- acting through the AhR- there is controversy for the role of the AhR in cancer development. In some studies, the AhR acts as a potent tumor suppressor, recently being shown to repress melanoma growth55, liver carcinogenesis56 and inflammation-associated colorectal tumorigenesis57. Genetic variations in AHR are also implicated in lung cancer susceptibility amongst smokers, where such variation may affect AhR protein expression and/or activity585960.…”
Section: Discussionmentioning
confidence: 99%
“…Although dioxin is classified as a human carcinogen- acting through the AhR- there is controversy for the role of the AhR in cancer development. In some studies, the AhR acts as a potent tumor suppressor, recently being shown to repress melanoma growth55, liver carcinogenesis56 and inflammation-associated colorectal tumorigenesis57. Genetic variations in AHR are also implicated in lung cancer susceptibility amongst smokers, where such variation may affect AhR protein expression and/or activity585960.…”
Section: Discussionmentioning
confidence: 99%
“…Disease models in which AHR modulation has been suggested as a possible target include, for instance, cancer, Crohn's disease, ulcerative colitis, diabetes, MS and inflammatory skin conditions such as atopic dermatitis (Benson and Shepherd 2011, Díaz-Díaz, et al 2016, Furumatsu, et al 2011, Haas, et al 2016, Jin, et al 2014, Kerkvliet, et al 2009, Quintana, et al 2010, Singh, et al 2007, Van Den Bogaard, et al 2013 . Although the mechanisms of action of the parent compounds of C1 and C3, laquinimod and tasquinimod, are not yet fully elucidated, they are recognised as immunomodulatory compounds (Raymond, et al 2014, Varrin-Doyer, et al 2014.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…These impacts are particularly related to immunomodulation (Zhu, et al 2014). Appropriate activation of AHR, devoid of TCDD-like toxicity, could thus lead to novel therapeutics for treatment of, for instance, cancer, multiple sclerosis (MS), inflammatory skin diseases, Crohn's disease and colitis (Arsenescu, et al 2011, Benson and Shepherd 2011, Díaz-Díaz, et al 2016, Furumatsu, et al 2011, Haas, et al 2016, Jin, et al 2014, Quintana, et al 2008, Van Den Bogaard, et al 2013.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The loss of AhR by crossing APC Min/+ with AhR −/− mice enhances intestinal tumor formation and treatment of APC Min/+ mice with AhR ligands [e.g., cruciferous vegetable-derived I3C and DIM] inhibits tumor formation [221]. Similar results indicating that AhR is a repressor of inflammation-associated colon cancer have also been recently described [230]. Collectively, these findings clearly demonstrate that the AhR and its dietary and microbial-derived ligands have a profound impact on gastrointestinal homeostasis and tumorigenesis.…”
Section: Dietary Mediators Of Colon Tumorigenesismentioning
confidence: 55%